2019
DOI: 10.1098/rstb.2018.0543
|View full text |Cite
|
Sign up to set email alerts
|

Ecological pressures and the contrasting scaling of metabolism and body shape in coexisting taxa: cephalopods versus teleost fish

Abstract: Metabolic rates are fundamental to many biological processes, and commonly scale with body size with an exponent ( b R ) between 2/3 and 1 for reasons still debated. According to the ‘metabolic-level boundaries hypothesis', b R depends on the metabolic level ( L R ). We test this prediction and show that across ceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 57 publications
2
35
0
Order By: Relevance
“…2017), but current research suggests it may reflect the scaling of selective pressures on life‐history traits (Harrison 2017; Tan et al. 2019). Likewise, it has been suggested that the dimensionality of foraging space (2D or 3D) drives the scaling of consumption rate (Pawar et al.…”
Section: Discussionmentioning
confidence: 99%
“…2017), but current research suggests it may reflect the scaling of selective pressures on life‐history traits (Harrison 2017; Tan et al. 2019). Likewise, it has been suggested that the dimensionality of foraging space (2D or 3D) drives the scaling of consumption rate (Pawar et al.…”
Section: Discussionmentioning
confidence: 99%
“…A 1 12) of O.dioica during ontogenetic growth prompts suggestions about the selective effects on growth of mortality risk in an open-water environment. With no refuges from predators, rapid sustained uptake of resources may be required to reach maturity fast before being consumed 79,80 . The scyphozoan Pelagia noctiluca also exists within a high-mortality pelagic environment but instead exhibits a shallower mass-scaling of biosynthesis potential ( = .…”
Section: Discussionmentioning
confidence: 99%
“…predation) that exist between benthic and pelagic habitats of aquatic invertebrates may affect the mass-scaling of an organism's uptake of resources. For example, high predation risk throughout ontogeny in the sunlit epipelagic zone, which lacks refuges from predators, may lead to the evolution of steeper mass-scaling of resource uptake, compared with more benthic conditions where invertebrates can reduce predation risk by finding refuge [78][79][80] . The diversity in the mass-scaling of biosynthesis potential makes benthic and pelagic invertebrate species two ideal groups to explore variation in the mass-scaling exponent of biosynthesis potential A ( ) when fitting the VBGF.…”
Section: The Data Setmentioning
confidence: 99%
“…For most teleosts, the scaling exponent of RMR (b R ) ranges between 0.65 and 0.95 (Bokma, 2004;Clarke & Johnston, 1999;Killen, Atkinson, & Glazier, 2010;Luo et al, 2015). Many hypotheses have been proposed to explain allometric scaling and whether the scaling exponent b has a constant value, including the surface area hypothesis (Glazier, Hirst, & Atkinson, 2015;Hirst, Glazier, & Atkinson, 2014;Okie, 2013;Rubner, 1883;Tan, Hirst, Glazier, & Atkinson, 2019), the organ size hypothesis (Itazawa & Oikawa, 1983;Oikawa, Takemori, & Itazawa, 1992), the metabolic theory of ecology (Brown, Gillooly, Allen, Savage, & West, 2004;West, Brown, & Enquist, 1997), the cell metabolism hypothesis (Davison, 1955;Kozłowski, Konarzewski, & Gawelczyk, 2003;Shestopaloff, 2016;Starostová, Konarzewski, Kozłowski, & Kratochvíl, 2013), and the metabolic-level boundaries hypothesis (Glazier, 2005(Glazier, , 2008(Glazier, , 2009(Glazier, , 2010. These hypotheses can partially explain the allometric scaling of MR, but multiple causes may play a role (Glazier, 2014a(Glazier, , 2014b.…”
Section: Introductionmentioning
confidence: 99%